Innovation-driven strategic partnership between industry and academia in nurturing the growth of technology for global halal sector - Ismail, Alyani (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
What is more interesting about the concept of halal food and sustenance mentioned in the Al-Quran is the adjective "toyyib" which follows. Toyyib (or toyyibah; toyyibat or tuuba as plural) in terms of the meaning, is something good or the opposite of bad. So, if the so-called "halalantoyyiban", it means something that is Halal that comes with it the goodness. There are four (4) places in the Qur'an where Allah use ‘toyyib’ as an adjective to describe Halal food or sustenance, in Surah al-Baqarah, verse 168; Surah al-Maaidah, verse 88; Surah al-Nahl, verse 114 and Surah al-Anfal, verse 69. Islam asserts that things that are “barakah” may spread goodness to many people for a long period of time. Indeed, efforts to look for Halal and good sustenance form one economic power at the level of individuals, society and nation, that it must serve as the basis of life as one that needs to be achieved by each individuals as well as a government. The terms “look for Halal and good sustenance” itself represents the importance of innovation for Halal, and thus comes with it the “effort to look for Halal and good sustenance”, literally means that this has created a demand of consumers from the economic perspective. Innovation is the most important way of taking Halal food to the next level. Innovation comes with it the utilization of technology, and the utilization of technology comes with it economic growth. The wisdom of Islam demands that Muslims are to equip themselves to economic strength, since it is linked to the top element in the rank of “maslahahdaruriyah”, that is to maintain the sanctity of Islam and faith on an individual. To bring technology to innovation requires intense research. The route for research to innovation would require strategic partnership between academia and industry as the main players in Halal industry. With innovation, Halal market player (industry) can identify new opportunities that by searching a gap in the market, a new trend and changes in customer behaviour. To attain this level, Halal entrepreneurs should be always screening several ideas into a manageable number of high potential options for further development, and for academicians to take this further in their research and development. This mutual understanding and partnership will only be materialised through the innovation-driven partnership model between industry and academia.